Kondisi Resirkulasi Udara terhadap Penurunan Sumber Panas di Dalam Tambang Bawah Tanah (Jurnal Geomine, 2020)
A condition that often occurs in a mine is the use of local ventilation fans which causes air circulation (recirculation). This of course can make the working environment conditions hot. A model is needed that can describe air movement, so that we can easily find out the working conditions of the ventilation network in the mine. The research was conducted at work sites that use quite a lot of local fans but the results of high temperature measurements. After analyzing the simulation of the ventilation network modeling, the air recirculation occurs by 50%. This has an effect on decreasing the length of time the heat source operates, it is evident from the results of the analysis carried out with a numerical approach that the air temperature will increase when the heat source operates by ± 2°C (32.6°C to 34.5°C) only in time 1.5 hours. The air temperature will drop again when the heat source stops operating with an average of 0.1°C/hour.